Biofilm immobilization of Clostridium acetobutylicum on particulate carriers for acetone-butanol-ethanol (ABE) production. (September 2018) - Zhou, Wencan; Liu, Jingyun; Fan, Senqing; Xiao, Zeyi; Qiu, Boya; Wang, Yuyang; Li, Jianfeng; Liu, Yicai
Abstract: Biofilm immobilization of Clostridium acetobutylicum CICC 8012 on active carbon, bagasse and bricks was carried out for ABE production. The cells could be well immobilized on surface of the carriers to form the biofilm and the sugarcane bagasse exhibited 'bamboo node' structure with bacillus migrating from one 'bamboo node' to another. Obvious higher cell concentration than that in free cell fermentation was achieved. Different fermentation performances were observed with those three cell immobilization carriers. The best fermentation performance was achieved in the case of with bagasse as the carrier, in which 10.21 g/L of total solvents concentration (5.8 g/L of butanol), 0.42 g/g of yield and 0.32 g/L/h of productivity has been obtained. Compared with free cell fermentation, butanol concentration, butanol yield and butanol productivity were increased by 2.47%, 41.7% and 66.7%, respectively. The results indicated that enhanced ABE fermentation was accomplished with bagasse as cell immobilization carrier. Graphical abstract: Unlabelled Image Highlights: Biofilm immobilization of Clostridium acetobutylicum CICC 8012 for ABE production Morphology and microstructure of biofilm on particulate carriers were identified. Bacillus migrated from one 'bamboo node' to another with biofilm on sugarcane bagasse High cell concentration with high immobilization ratio was achieved. Enhanced ABE fermentation was achieved with higher yield and productivity.